The Paraboloidal Reflector Antenna in Radio Astronomy and Communication Theory and Practice - Baars, Jacob W. M. (Astrophysics and Space Science Library, 2007)
Reflector antennas are widely used in the microwave and millimeter wavelength domain. Radio astronomers have developed techniques of calibration of large antennas with radio astronomical methods. These have not been comprehensively described. This text aims to fill this gap. The Paraboloidal Reflector Antenna in Radio Astronomy and Communication: Theory and Practice takes a practical approach to the characterization of antennas. All calculations and results in the form of tables and figures have been made with Mathematica by Wolfram Research. The reader can use the procedures for the implementation of his/her own input data. The book should be of use to all who are involved in the design and calibration of large antennas, like ground station managers and engineers, practicing radio astronomers, and finally, graduate students in radio astronomy and communication technology.